PARTICIPATION DES ORGANISATIONS DE LA SOCIETE CIVILE DANS LA GOUVERNANCE DES REGIONS POST-CONFLIT. CAS DE LA PROVINCE DE L’ITURI EN RDC - WAROM JANVIER; UFOY WATHUM; UYEWA, KAKURA (IJRDO - Journal of Social Science and Humanities Research, 2021)
State management is nowadays put between political society and civilian one; especially in the post conflict areas, so many actors imply themselves in order to better social, economic and political problems. Thus, mecanisms of participation to this different management from one society to another, political society uses constitutional mecanisms; whereous, civilian society uses mechanisms related to circumstance. We expect, descended from this study relieving the limits of citizen participation and mentioning concret actions led by OSC for Iturian leadership. In Ituri, OSC participation in process of dealing with peace is realized throughout citizen actions menaged by OSC for stabilizing situation, public meetings (49.5%), opened letters (24%), clames (20.6%), strike (2.1%), civilian disobedience (1.4%), day without information (0.7), anger marching and governor’s call out (0.3%) have been used during under exam period by OSC for this objective. However, we have noticed the field character of participation mixed of population that domages agents’ list to commun strategy to members of OSC due to members of OSC due to fight for a good leadership of obstacles to OSC participation related to politisation and acters’ miscleading and also concerned with acters’ missecurity as major obstacles that limit OSC participation in the leadership of post-conflict regions.